Hodgkins Lymphoma in Crohns Disease Treated with Infliximab - Carvalho,Diana (2017)
Introduction: Lymphoproliferative disorders, particularly non-Hodgkins and Hodgkins lymphomas, are rare in patients with inflammatory bowel diseases. The use of thiopurines and infection by Epstein-Barr virus are well-known cofactors that can raise its prevalence. Other risk factors such as disease activity and biological treatment are the subject of discussion, without enough data in the literature to confirm a potential association. Methods: We report a case of Hodgkins lymphoma in a patient who had been treated with azathioprine and was on long-term monotherapy with infliximab. Conclusions: We stress the importance of recognizing the possible occurrence of a lymphoproliferative disorder in association with anti-tumor necrosis factor-α therapy.